The limitations on the right to strike introduced by Law No. 9808 in light of the principle of non-regression - Campos Rodríguez, Claudia María (2025)
This article analyzes the compatibility of certain provisions of the “Law to Provide Legal Certainty on Strikes and Their Procedures” (hereinafter, “Law No. 9808”), approved in Costa Rica in 2020, with the principle of non-regression. This principle prohibits the implementation of regulations that reduce the level of protection of acquired rights unless a valid justification exists. The analysis concludes that most of the provisions reviewed unjustifiably limit the right to strike and, therefore, fail to meet the “non-regression test”, constituting a violation of the principle of non- regression.